INTOLERABLE ACTS: AN ANALYSIS OF THE LAW RELATING TO ONLINE CHILD PORNOGRAPHY IN UGANDA (The Pretoria Student Law Review, 2021)
In Uganda computers are beginning to form an integral part of the social and economic life of the people. Computer based social media such as Facebook, WhatsApp and Twitter are increasingly getting more subscribers in Uganda, many of them being children. Internet penetration and legitimate usage has grown in tandem with internet abuses such as online child pornography. The risk of child sexual abuse in Uganda is considerably high with 77.7% of the primary school children and 82% of the secondary school students having experienced sexual abuse at school. 51% of victims were aged between 10 and 13 years, and 40.6% between 14 and 17. Now, the internet enables virtually anyone to communicate privately with children in their homes. Ironically, parents concerned about threats from ‘strangers’ may erroneously believe that their children are safer inside the home and on the computer. While a search on ‘child pornography’ on a web search engine, such as Google, would normally only produce sites campaigning against the availability of child pornography on the internet, child pornography thrives in channels devoted to it within the internet Relay Chat, ICQ environment and on peer to peer (P2P) file sharing systems and can sometimes be found in ‘spam’ e-mails.
Keywords: Uganda; social media; child sexual abuse; online child pornography